2022
DOI: 10.3892/ol.2022.13309
|View full text |Cite
|
Sign up to set email alerts
|

Ki67 for evaluating the prognosis of gastrointestinal stromal tumors: A systematic review and meta‑analysis

Abstract: Overexpression of Ki67 is observed in tumor cells, and it has been suggested to be a marker for cancer prognosis. However, the relationship between Ki67 expression and the risk of recurrence of gastrointestinal stromal tumors (GISTs) remains poorly defined. In the present study, a meta-analysis was used to examine the associations between Ki67 levels and GIST recurrence. Studies reporting GIST and Ki67 were found by searching Cochrane Library, PubMed and Embase until October 14, 2021. The Newcastle-Ottawa Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
(55 reference statements)
3
5
0
Order By: Relevance
“…The Ki-67 index can serve as an important reference for evaluating the tumor risk classification. A close relationship between the expression level of Ki-67 and the prognosis of GIST was also identified in a large-sample meta-analysis, with a higher rate of Ki-67 related to worse patient prognosis (29); this is consistent with our main findings. Another large-sample retrospective analysis found that the prognosis of high-risk patients with high Ki-67 expression was significantly worse than that of patients with low Ki-67 expression (30).…”
Section: Discussionsupporting
confidence: 91%
“…The Ki-67 index can serve as an important reference for evaluating the tumor risk classification. A close relationship between the expression level of Ki-67 and the prognosis of GIST was also identified in a large-sample meta-analysis, with a higher rate of Ki-67 related to worse patient prognosis (29); this is consistent with our main findings. Another large-sample retrospective analysis found that the prognosis of high-risk patients with high Ki-67 expression was significantly worse than that of patients with low Ki-67 expression (30).…”
Section: Discussionsupporting
confidence: 91%
“…The expression of Ki67 is strongly associated with tumor cell proliferation and growth and has been widely used in the assessment of tumors. , Here, Ki67 protein levels decreased significantly in tumor tissues from the N1 -lighted and NG2 -lighted groups, as well as those in tumor tissues from the N-cRGD -lighted and NG-cRGD -lighted groups, which further verified their antiproliferative activity (Figure G). Furthermore, hematoxylin and eosin (H&E) staining of tumor tissues revealed prominent cell death in the N1 -lighted, NG2 -lighted, N-cRGD -lighted, and NG-cRGD -lighted groups displaying their in vivo antitumor activity with light illumination, while no obvious cell damage was observed in the control groups (Figure H).…”
Section: Resultssupporting
confidence: 60%
“…Another investigation discovered that Ki-67 expression levels were markedly elevated in gastric cancer tissues compared to adjacent tissues. Moreover, a significant positive correlation was observed between Ki-67 expression and tumor infiltration, lymph node metastasis, and staging in gastric cancer cases [27]. In this study, pathological pattern, histological grade, clinical stage, invasiveness, and lymph node metastasis were related to the positive expression rate of Ki-67 and PFN1.…”
Section: Discussionsupporting
confidence: 53%